1996
DOI: 10.1159/000201328
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of Gastric Surface Mucous Cell Line GSM06 from Transgenic Mice Harboring Temperature-Sensitive Simian Virus 40 Large T-Antigen Gene

Abstract: We investigated the biological features of gastric surface mucous cell line GSM06, established from transgenic mice harboring the temperature-sensitive simian virus 40 large T-antigen gene. GSM06 cells grew until confluent monolayers were formed at the permissive temperature (33 °C), showing that the cessation of cell growth may be due to contact inhibition. Moreover, the cells did not grow in a soft agar gel. However, chromosome numbers of the cells were not normal. When GSM06 cells were cultured in Daigo’s T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…Moreover, RGE1-22 cells produced PGE 2 . These gastric epithelial characteristics of the cells were comparable to those of GSM06 cells (Sugiyama et al, 1993;Tabuchi et al, 1996). In all cells established here, nonpermissive temperature decreased expression level of large T-antigen and arrested cell growth.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, RGE1-22 cells produced PGE 2 . These gastric epithelial characteristics of the cells were comparable to those of GSM06 cells (Sugiyama et al, 1993;Tabuchi et al, 1996). In all cells established here, nonpermissive temperature decreased expression level of large T-antigen and arrested cell growth.…”
Section: Discussionsupporting
confidence: 72%
“…When the cells were cultured on a cell culture insert at 33°C, TER was detected in RGE1-01, RGE1-02, RGE1-03, RGE1-21, RGE1-22 and RGE2-01 cells, with levels of the 137, 6.1, 47.1, 85.7, 58.6 and 34.3 Ω/cm 2 , respectively. The level of TER of RGE1-01 was comparable to that of canine kidney MDCK (TER = 100 Ω/cm 2 ) (Cereijido et al, 1980) and porcine kidney LLC-PK1 cells (170 Ω/cm 2 ) cells (Hull et al, 1976), and was smaller than that of GSM06 cells (790 Ω/cm 2 ) (Tabuchi et al, 1996). On the other hand, nonpermissive temperature markedly decreased the TER in five cells (Fig.…”
Section: Measurement Of Ter and Pgementioning
confidence: 56%
See 2 more Smart Citations
“…Morphologically, GSM06 cells are rounded or polyhedral, as is typical of primary cultured gastric surface mucous cells (3,8,24,42). Electron microscopy revealed that the cells contain a small number of secretory granules (20,38). Immunologic studies indicate that the GSM06 cells are positive for PAS and class I concanavalin A but negative for H,K-ATPase and class III concanavalin A (37).…”
Section: Discussionmentioning
confidence: 99%